The Integration of Hybrid and Game-Based Learning in Physics Education: A Systematic Review of Their Effects on Critical Thinking and Problem-Solving Skills (2018 - 2024) - Efi Kurniasari; Sugiyarto Surono; Ishafit Ishafit; Dian Artha Kusumaningtyas; Dwi Sulisworo (Indonesian Review of Physics, 2025)
This study aims to analyze the impact of integrating hybrid and game-based learning on critical thinking and problem-solving skills in physics education and to identify research trends from 2018 to 2024. The method used was a systematic literature review following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The literature search was conducted through Scopus, Web of Science, and Accredited National Journals databases using a combination of relevant keywords. Inclusion criteria included empirical research articles published in English or Indonesian between 2018 and 2024. The selection process involved the stages of identification, screening, eligibility assessment, and inclusion. A total of 16 articles were analyzed further. Data were analyzed using thematic synthesis techniques to identify patterns, methodological trends, and key findings from the reviewed studies. The results indicate that hybrid learning has a more consistent impact on enhancing critical thinking and problem-solving skills, particularly through problem-based approaches and technological support. Meanwhile, game-based learning contributes more to improving motivation, engagement, and understanding of physics concepts. This study contributes a thematic synthesis and comparative analysis of the integration of hybrid and game-based learning and serves as a conceptual foundation for the development of technology-based physics learning models to enhance critical thinking and problem-solving.